Akurasi Penjurusan Bidang Keahlian Teknik Komputer dan Informatika Menggunakan Metode SAW - Monsya Juansen; Sarjon Defit; S Sumijan (Rektorat Universitas Putra Indonesia YPTK Padang, 2020)
Many students choose majors because of joining friends, because of the popularity of majors and other reasons even though the chosen majors are not in accordance with their talents. This research is expected to provide solutions to students regarding the majors they will choose. If this problem can be overcome then it will greatly affect both students and schools, the impact on students will be increased enthusiasm and enthusiasm for learning, for schools the impact will be the development of every department there is because the output produced is competent students because of the knowledge delivered right on target. This research is expected to minimize the mistakes in the selection or determination of student majors by applying the SAW method, can determine what variables determine the accuracy of the majors separation by applying the SAW method. The data tested on this system is the data of Bengkulu 1 Vocational School students as many as 100 student data on the Computer and Information Engineering skills program. he data that is processed in this system is the data of Bengkulu 1 Vocational School students as many as 204 student data on the Computer Engineering and Information Technology expertise program. The method of decision making in the system is the Simple Additive Weighting method. The results of testing this method from 204 test data performed for an accuracy of 94,61%. The high accuracy obtained from testing the data so that this system is very suitable to be used to determine the majors of students of SMKN 1 Kota Bengkulu in the field of Computer and Information Engineering expertise.